Human immunodeficiency virus: The potential of medicinal plants as antiretroviral therapy. Issue 6 (25th February 2022) - Shahzad, Muhammad; Chen, Huan; Akhtar, Tasleem; Rafi, Ali; Zafar, Muhammad Shoaib; Zheng, Yong‐Tang
Abstract: Human immunodeficiency virus (HIV) infection is fast becoming widespread in the world with 37.7 million people living with HIV in 2020. Antiretroviral therapy involving chemical drugs has declined acquired immunodeficiency syndrome (AIDS)‐related mortality and improved the life quality of AIDS/HIV sufferers. However, the emergence of drug resistance and side effects are the main obstacles for the long‐term use of these chemicals as antiretroviral therapy. Recently, a lot of emphasis is being put on finding naturally occurring drug candidates that show activity against HIV and can be potentially used as antiretroviral therapy. In this study, different medicinal plants, Pistacia khinjuk, Teucrium stocksianum, Uncaria tomentosa, Pistacia integerrima, Trigonella gharuensis, and Artocarpus lakoocha, were explored for their anti‐HIV potential. Syncytium and p24 assays were performed to determine antiviral activity, while the MTT assay was used to determine cytotoxicity. Results showed that extracts from all six plants inhibited HIV replication in vitro. Also, extracts from Pistacia khinjuk, Teucrium stocksianum, Uncaria tomentosa, and Pistacia integerrima showed low cytotoxicity with a 50% cytotoxicity concentration value of >200 μM. Results of this study indicate that there is potential in these natural extracts to become candidate drugs to be used as complementary and alternative medicine for HIV infection. Highlights: Important findings with reference to anti‐human immunodeficiency virus (HIV) activities and cytotoxicities of extracts from six different plants. Extracts from all six plants inhibited HIV replication in vitro. Pistacia khinjuk (concentration required for the effectiveness of 50% [EC50 ] = 0.34 µM) and Teucrium stocksianum (EC50  = 0.57 µM) showed the highest anti‐HIV activities. These natural extracts have the potential to become candidate drugs to be used as a complementary and alternative medicine for HIV.